Mechanical restraint x humanization: nursing contributions to mental health care in the hospital environment - Figueiredo Júnior, Júlio César; Santos, Larissa Christiny Amorim dos; Alves Ribeiro, Wanderson; Lima, Luciene Aparecida Campos; Diva de Oliveira, Marina; Bruno de Jesus , Frandieison; Costa de Morais, Maicon; Paula, Enimar de (Brazilian Journal of Science, 2022)
The treatment of people in psychological distress raises discussions and contradictions related to humanization, especially during the execution of procedures such as mechanical restraint. It has been used historically by health services without taking into account the numerous consequences that its use may entail, often used indiscriminately and non-reflectively. The objective for the elaboration of this study was to reflect on the role of the nursing professional in the conduct of mechanical restraint in relation to humanization, considering the consequences for mental health. This is a narrative literature review in the databases of the Virtual Health Library (VHL): International Health Science Literature (MEDLINE), Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature on Health Sciences. Health (LILACS), among others. The use of mechanical restraints has been found to increase the risk of post-fall injury and other undesirable damage, rather than preventing it. Being linked to serious adverse events such as hip fractures; bruise; limb dislocation; ischemic injuries to the hands and arms. Hurting the rights of the citizen, pride, soul and flesh of those who are subjected to such a situation. It affects deep lacerations in the care of the team, in the culture of caring, caring with love, with humanization. Where containment, whether mechanical, chemical or biological, challenges the dignity of the human person, since it cannot speak of freedom, peace or development of a person who is contained. In this way, a therapeutic approach based on a humanized and unique assessment is essential, which requires skill and speed from professionals to take action, always maintaining good communication in a humanized way, listening to their patients calmly, avoiding as much as possible the use of restraints